Standardization of Mass Production Technique for VA Mycorrhiza - Saritha V Elizabeth (Department of Plant Pathology, College of Agriculture, 1999)
Different methods to standardize the mass inoculum production techniques of AMF was attempted in the present investigation. Effort to identify suitable substrate combination indicated that a substrate combination consisting of basal medium of vermiculite 65 per cent, perlite 20 per cent, cowdung 5 per cent and soil 10 per cent as components was ideal for maximum AMF spore production as well as for plant growth. Mycorrhizal setaria plant was found to be the ideal host for biomass production while maximum AMF spore count was obtained with stylosanthes, which possessed only less root volume. A host combination of congosignal and stylosanthes was found to be the ideal system for achieving maximum AMF colonization and spore production apart from increased plant growth and biomass. Application of different plant growth regulators stimulated plant growth, biomass production and AMF spore production. Foliar application of humic acid 2000 ~l r' resulted in maximum increase in spore production and hence can be recommended for application in routine AMF inoculum production systems. Induction of stress to the host plants using different stress inducing substances stimulated AMF sporulation. Water stress induced on 75 DAP resulted in maximum spore production. The stress inducers which increased spore production also include ethrel 25 ul r', NaCI 0.5, 1.0, 1.5 per cent and ABA 2.0 mg r ' treatments.